Implementasi profil pelajar pancasila dimensi gotong royong dalam pembelajaran IPAS kelas V di sekolah dasar - Sherlina Oktavia Agatha; Retno Winarni; Supianto Supianto (Universitas Sebelas Maret, 2024)
This research aims to describe the implementation of the Pancasila student profile dimension of mutual cooperation in science and science learning for class 5B at elementary school Kestalan Surakarta. This research is analytical descriptive qualitative research. The implementation of the mutual cooperation dimension using the STAD cooperative model in science and science learning for class 5B at elementary school Kestalan Surakarta, which was carried out over three lessons, has been implemented very well by teachers who obtained an average percentage of 81.4%. The teacher has implemented all aspects and indicators of the STAD type cooperative learning model in science learning from opening to closing. The students' mutual cooperation attitude appeared to be very good with an average percentage of 82.68%. All aspects of the mutual cooperation dimension which includes aspects of collaboration, caring and sharing have emerged when researchers conducted observations on students. However, there are still less visible indicators. Thus, further efforts are needed, such as teachers in implementing the mutual cooperation dimension using the STAD cooperative model, should be more innovative and provide more in-depth assistance during group learning. Students should have high motivation, so that they are more serious and actively involved when discussing in groups.